104k views
3 votes
Solve with quadratic formula

3x+6x+3=0

6x^2-2x+1=0

2x^2+4=0

-3x=2x^2-4

-5x^2-6=-4x​

1 Answer

2 votes

Answer:

Explanation:

3x+6x+3=0

9x+3=0

9x=0-3

9x=-3

x=-3/9

simplify

x=-1/3

Answer: x=-1/3

------------------------

6x^2-2x+1=0

Apply the quadratic formula with a=6, b=-2 and c=1.

Answer: (1+sqrt(5)*i)/6, (1-sqrt(5)*i)/6

--------------------------------------------------

2x^2+4=0

2x^2=0-4

2x^2=-4

x^2=-4/2

x^2=-2

x=i*sqrt(2), -i*sqrt(2)

Answer: i*sqrt(2), -i*sqrt(2)

----------------------------------------

-3x=2x^2-4

2x^2-(-3x)-4=0

2x^2+3x-4=0

Apply the quadratic formula with a=2, b=3 and c=-4.

Answer: (-3+sqrt(41))/4, (-3-sqrt(41))/4.

--------------------------------------------

-5x^2-6=-4x

-5x^2-(-4x)-6=0

-5x^2+4x-6=0

5x^2-4x+6=0

Apply the quadratic formula with a=5, b=-4 and c=6.

Answer: (2+sqrt(26)*i)/5, (2-sqrt(26)*i)/5.

User Rudivonstaden
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.